Spatial patterns of recreational exploitation in eastern Australian ROFAs: implications for zonal management. (7th September 2014) - Ochwada‐Doyle, F. A.; Mcleod, J.; Barrett, G.; Clarke, G.; Gray, C. A.
Abstract Effective management of recreational fisheries requires information on fine‐scale spatial patterns of recreational exploitation. Such information is particularly important for specially designated regions such as recreational‐only fishing areas (ROFAs). Using data acquired through progressive counts and interview‐based surveys, this study quantitatively compared recreational effort, harvest‐per‐unit‐effort (HPUE) and species composition among zonal habitats in three representative estuarine ROFAs in eastern Australia. The zones compared were as follows: (1) entrance channels; (2) lake areas; (3) artificial reefs; (4) tributary creeks; (5) rivers; and (6) canals. In most cases, effort was concentrated in the lake zones, which had the greatest access to fisheries resources. The lake and channel zones were associated with some of the highest HPUEs for key taxa [Acanthopagrus spp. (hybrid complex of Acanthopagrus butcheri (Munro) × Acanthopagrus australis (Owen)), Platycephalus fuscus (Cuvier), Sillago ciliata (Cuvier) and Girella tricuspidata (Quoy & Gaimard)] and a greater number of highly sought‐after species. Drawing on specific examples from these findings, this paper concludes by illustrating how spatial information on exploitation gained from this type of research can be used to meet the fundamental goals of recreational fisheries management at fine spatial scales.